2020
DOI: 10.5851/kosfa.2020.e10
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the pH and Salt Concentrations on Physicochemical Properties of Pork Myofibrillar Protein Gels Added with Cornstarch

Abstract: The aim of this study was to evaluate quality characteristics of pork myofibrillar protein (MP) added with cornstarch as affected by different pH values and salt cocnentrations. MP mixtures were prepared with three different pH values (pH 6.00, 6.25, and 6.50) and three different salt concentrations (0.15, 0.30, and 0.45 M). Cooking yield (CY), gel strength, viscosity, and scanning electron microscopy were measured to evaluate characteristics of MPs. CYs of MPs with cornstarch at above pH 6.25 or salt 0.30 M w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Unlike our results, Abdelhakam et al (2019) reported that the cooking yield of pomace patties at 2% and 4% of red grapes pomace showed higher values than control patties. These conflicting results might be explained by the patty pH ~1 unit higher than ours in addition to the incorporation of several ingredients into their patties such as salt, pepper and cumin (Lee & Chin, 2020).…”
Section: Ph and Cooking Yieldcontrasting
confidence: 67%
“…Unlike our results, Abdelhakam et al (2019) reported that the cooking yield of pomace patties at 2% and 4% of red grapes pomace showed higher values than control patties. These conflicting results might be explained by the patty pH ~1 unit higher than ours in addition to the incorporation of several ingredients into their patties such as salt, pepper and cumin (Lee & Chin, 2020).…”
Section: Ph and Cooking Yieldcontrasting
confidence: 67%
“…Similarly, Rios-Mera et al, [32] informed that beef burgers with a sodium chloride reduction of 50 and 75% had a cooking loss higher than 39% while the control sample was 33%. These values obtained were expected since sodium chloride is added to meat products and has the property of solubilizing myofibrillar proteins to increase their hydration and water-holding capacity [33]. In this sense, a low sodium chloride concentration affected the heat-induced gelation in meat products as a result of low myofibrillar protein dissolution.…”
Section: Cooking Propertiesmentioning
confidence: 68%
“…The pH value could affect the biological tolerance and stability of formulations [ 24 ]. The pH of TCMs could limit the growth of microorganisms, contributing to the stability [ 25 , 26 ]. For ZSS samples, the pH value of rancid samples was slightly lower than that of normal samples.…”
Section: Resultsmentioning
confidence: 99%